Binding of Fiduciary Guarantee on Pegadaian Kredit Products Fiduciary Installments (Kreasi) at PT Pegadaian (Persero) After the Enactment of Minister of Finance Regulation Number 130/OMK.010/2012 - Holilurrohman, Holilurrohman (Universitas Syiah Kuala, 2023)
The motivation behind this exploration is to grasp the significance and comprehension of the execution of Pegadaian Kreasi items at PT PEGADAIAN (Persero). The strategy utilized is a juridical way to deal with investigate different regulations and guidelines connected with the execution of guardian ensures which are a relationship of issues among banks and borrowers when the debt holder defaults. In the mean time, a standardizing approach is utilized to examine regulation which is viewed as designed social conduct in the existences of individuals who generally cooperate. The consequences of this exploration show that the utilization of Regulation Number 42 of 1999 to Pegadaian Kreasi Items completed by PT PEGADAIAN (Persero) has not been carried out as it ought to. In numerous monetary foundations, trustee ensures are as yet made secretly and are not enrolled with the KPF. The large costs associated with creating and registering fiduciary guarantees, the absence of a mandatory registration time limit, and the absence of sanctions for not registering fiduciary guarantees (with the exception of Financing Institutions) are among the factors that contribute to the discrepancy between the provisions of the guarantees and their actual application. On this premise, PT PEGADAIAN (Persero) in running the Guardian Portion Credit Pegadaian item (Kreasi) can be legitimate in carrying out a strategy not to quickly enroll trustee ensures with KPF (Business Judgment Rules).